Korelasi Kreatifitas Guru dengan Hasil Belajar Siswa pada Bidang Studi Akidah Akhlak di MAS Bonjol - Ranjani Hendryan; Arifmiboy Arifmiboy (LP3M KH Yazid Karimullah Institute, 2023)
This research was conducted at MAS Bonjol, the low learning outcomes of students in the field of study of moral beliefs even though the teacher's level of creativity is already high is the background to the problem that must be investigated. The aim of this research is to examine the creativity of Aqidah Akhlak teachers at MAS Bonjol, the learning outcomes of Aqidah Akhlak at MAS Bonjol, and to find out the important relationship between teacher creativity and the learning outcomes of Akidah Akhlak students at MAS Bonjol. This problem was researched using quantitative research methods which are correlative in nature. Data was collected using questionnaire research instruments and documentation. The population and sample in this research were female students in classes X and XI of MAS Bonjol. Based on the research conducted, the results obtained showed that there was a relationship between variables X and Y with a low level of correlation. So, teacher creativity is not the main factor causing low learning outcomes for moral beliefs at MAS Bonjol.